Pyrene- and Bipyridine-based Covalent Triazine Framework as Versatile Platform for Photocatalytic Solar Fuels Production - Fávaro, Marcelo Alves; Yang, Jin; Ditz, Daniel; Küçükkeçeci, Hüseyin; Alkhurisi, Mohammed H.; Bergwinkl, Sebastian; Thomas, Arne; Quadrelli, Elsje Alessandra; Palkovits, Regina; Canivet, Jérôme; Wisser, Florian M. (ChemCatChem, 2023)
The ability to molecularly engineer materials is a powerful tool toward increasingly performing heterogeneous catalysts. Porous organic polymers stand out as photocatalysts due to their high chemical stability, outstanding optoelectronic properties and their easy and tunable syntheses. In photocatalysis, the insertion of photosensitizing π-extended molecules into molecularly well-defined donor-acceptor junctions is supposed to increase the catalytic activity, but yet remain experimentally underdeveloped. This study presents a pyrene-based Covalent Triazine Framework (CTF) synthesized through a polycondensation approach, which was designed to contain a molecularly-defined pyrene-triazine-bipyridine donor-acceptor-acceptor triad as the repetition unit of the CTF. The CTF is an efficient photocatalyst for hydrogen evolution from water reaching a significant production rate of 61.5 mmolH2/h/gcat. Moreover, the same CTF can easily be used as porous macroligand for an organometallic Rh complex to efficiently catalyze the carbon dioxide photoreduction into formic acid under visible light.
CRIS-Team Scopus Importer:2023-05-26
Keywords: condensation; covalent triazine framework; molecular control; photocatalysis; pyrene